2004
DOI: 10.1136/jcp.2004.017202
|View full text |Cite
|
Sign up to set email alerts
|

Sialometaplasia arising in the ectopic salivary gland ductal inclusions of multiple intraparotid lymph nodes

Abstract: Sialometaplasia, squamous metaplasia of salivary gland lobules, is a benign condition occasionally presenting with lesions clinically simulating malignancy. ''Necrotising sialometaplasia'', recognised by lobular infarction, necrosis, and simultaneous squamous metaplasia of ducts and acini is a well known condition. There are only a few reports of the ''proliferative type of sialometaplasia'', which is recognised by a more mature morphology of larger and more irregular metaplastic nests, lacking necrosis. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…In the latter study, Furuse concluded that calponin and SMA were the most consistent markers of myoepithelial cells in pleomorphic adenomas. In one case of sialometaplasia that occurred in salivary nodal inclusions, SMA and S100 staining at the periphery of the metaplastic lobules was noted, 15 but apart from this, myoepithelial markers have not previously been examined in NSM or its related lesions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the latter study, Furuse concluded that calponin and SMA were the most consistent markers of myoepithelial cells in pleomorphic adenomas. In one case of sialometaplasia that occurred in salivary nodal inclusions, SMA and S100 staining at the periphery of the metaplastic lobules was noted, 15 but apart from this, myoepithelial markers have not previously been examined in NSM or its related lesions.…”
Section: Discussionmentioning
confidence: 97%
“…Although necrosis is a defining feature in the description by Abrams, 5 most authors accept that it is likely to occur in the earliest stages and therefore may not always be seen by the time the patient comes to biopsy 1,12 . The lesion described as proliferative sialometaplasia shares many histological features with NSM, although in a distinct anatomical setting 15,16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sie führen durch ihre tumoröse Veränderung zu Symptomen und werden dadurch klinisch auffällig. Lymphoepitheliale Zysten, benigne lymphoepitheliale Läsionen sowie Sialometaplasien wurden im Bereich des intranodalen heterotopen Speicheldrüsengewebes beschrieben [6]. Bei der überwiegenden Mehrheit dieser heterotopen Speicheldrüsenläsionen handelt es sich jedoch um benigne Speicheldrüsentumoren, wobei das Zystadenolymphom (Warthin-Tumor) der Glandula parotis die häufigste Tumorentität darstellt [7].…”
unclassified